Strategi Penjualan di Aplikasi Tik Tok Dalam Perspektif Pemasaran Konvensional dan Pemasaran Syariah - Oktaviani, Lusi; Anwar, Zainul; Sholiha, Imroatus (Universitas Muhammadiyah Jember, 2023)
At the beginning of its emergence, TikTok was used as an entertainment medium for creation and for showing expression. However over time TikTok innovated in the form of TikTok Shop program which was also supported by attractive features—one of which was live streaming. Live streaming drives the number of TikTok users, especially TikTok shop users. Many competitors required the sellers on TikTok to implement strategies to market their products because marketing is the most important line in a business. There are several studies related to this research, but this research was deliberately written to find out how the sales strategy in TikTok which has been widely used and studied based on conventional and sharia marketing strategy. This research is a library research concentrating data sources on books, articles, journals, and etc. TikTok shop uses a marketing mix promotion strategy by using product strategy, pricing strategy, distribution strategy, and promotion strategy. Sales on TikTok also applies sharia marketing theory: the four characteristics, namely fathonah, amanah, shiddiq, and tabligh even though not all sellers apply it due to their various religions as well as their understanding of Islam. Therefore future researchers can carry internalization of understanding of the Islamic religion, especially in terms of mu'amalahAt the beginning of its emergence, TikTok was used as an entertainment medium for creation and for showing expression. However over time TikTok innovated in the form of TikTok Shop program which was also supported by attractive features—one of which was live streaming. Live streaming drives the number of TikTok users, especially TikTok shop users. Many competitors required the sellers on TikTok to implement strategies to market their products because marketing is the most important line in a business. There are several studies related to this research, but this research was deliberately written to find out how the sales strategy in TikTok which has been widely used and studied based on conventional and sharia marketing strategy. This research is a library research concentrating data sources on books, articles, journals, and etc. TikTok shop uses a marketing mix promotion strategy by using product strategy, pricing strategy, distribution strategy, and promotion strategy. Sales on TikTok also applies sharia marketing theory: the four characteristics, namely fathonah, amanah, shiddiq, and tabligh even though not all sellers apply it due to their various religions as well as their understanding of Islam. Therefore future researchers can carry internalization of understanding of the Islamic religion, especially in terms of mu'amalah